Hanya Holm The Biography of an Artist (Wesleyan University Press, 1969)
Known as one of the "big four" dance pioneers, Hanya Holm (born Johanna Eckert; 1893-1992) learned from, then worked with, Mary Wigman. Holm's interest in patterns and spactial dimensions influenced future dancers including Alwin Nikolais.